Profile of Shiga toxin-producing Escherichia coli strains isolated from dogs and cats and genetic relationships with isolates from cattle, meat and humans - Bentancor, Adriana (2012)
Fil: Bentancor, A. Cátedra de Microbiología, Facultad de Ciencias Veterinarias, Universidad de Buenos Aires; Argentina.